IberSPEECH 2021 2021
DOI: 10.21437/iberspeech.2021-3
|View full text |Cite
|
Sign up to set email alerts
|

An ASR-based Reading Tutor for Practicing Reading Skills in the First Grade: Improving Performance through Threshold Adjustment

Abstract: Automatic Speech Recognition (ASR) technology can potentially be employed to provide intensive practice and feedback to young children learning to read. So far there has been limited research on the use of ASR in the early stages of learning to read when children are still developing decoding skills. For this purpose, we developed an ASR-based system equipped with logging capabilities that can evaluate decoding skills in Dutch first graders reading aloud and provide them with instantaneous feedback. In a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In the previous study [3] we found that 48 was the threshold that produced the highest agreement between the ASR scores for correct/incorrect and the human judgment [3]. After removing invalid audio recordings, the best threshold shifted to 46.…”
Section: Performance Evaluation Of Different Systemsmentioning
confidence: 76%
See 3 more Smart Citations
“…In the previous study [3] we found that 48 was the threshold that produced the highest agreement between the ASR scores for correct/incorrect and the human judgment [3]. After removing invalid audio recordings, the best threshold shifted to 46.…”
Section: Performance Evaluation Of Different Systemsmentioning
confidence: 76%
“…The reading tutor used by pupils during the experiments made use of the Nov-oLearning ASR engine, in which the ASR model (ASR.1) was trained with Dutch adult speech. It calculates probability scores and gives right/wrong feedback according to the adjustable threshold [3]. Two other systems (system ASR.2 and system ASR.3) were built with Kaldi after the experimental tests with children.…”
Section: Asr Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in reading accuracy and speed were seen in different types of exercises [9]. After analyzing the data of this first experiment, we saw that a higher agreement between the system's scores and the judgements assigned by a human annotator could be obtained by adjusting the measures and thresholds in the system [10].…”
Section: Introductionmentioning
confidence: 88%